IMPROVING STUDENTS’ CRITICAL THINKING SKILLS THROUGH PROJECT-BASED LEARNING USING MINI SOLAR PANELS - Mukhammad Nur Kholishur Rofi'; Titin Sunarti (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2026)
Physics learning that still uses the lecture method causes students to have limited critical thinking skills. Therefore, this study examines the feasibility of learning, the improvement of critical thinking skills, and students’ responses to the implementation of the Project Based Learning (PjBL) model of mini solar panels on renewable energy material. This research design uses a pre-test post-test of one group tested on three classes as a replication. The implementation of the PjBL learning model of mini solar panels with the observed aspects on average for the three classes is 99.17%. The increase in students’ critical thinking skills shows a score of class X-H from 61.18 to 85.99; class X-F from 58.39 to 83.50; class X-D from 62.78 to 87.72. The average percentage of student questionnaire responses for the three classes is 94.52%, which is included in the Very Good category. Data analysis using normality test and produced normally distributed data, then continued with paired t-test in all three classes to test the hypothesis with results <0.05, so the initial hypothesis was rejected and showed significant differences in all three classes. N Gain analysis of the pre-test post-test results in all three classes showed a moderate category with an average of 0.698 for all three classes. From this research data, the application of the mini solar panel project-based learning model successfully improved critical thinking skills.